2016
DOI: 10.1109/tvcg.2015.2467191
|View full text |Cite
|
Sign up to set email alerts
|

Voyager: Exploratory Analysis via Faceted Browsing of Visualization Recommendations

Abstract: General visualization tools typically require manual specification of views: analysts must select data variables and then choose which transformations and visual encodings to apply. These decisions often involve both domain and visualization design expertise, and may impose a tedious specification process that impedes exploration. In this paper, we seek to complement manual chart construction with interactive navigation of a gallery of automatically-generated visualizations. We contribute Voyager, a mixed-init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
437
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(458 citation statements)
references
References 34 publications
3
437
1
1
Order By: Relevance
“…Data visualization management systems that automate and recommend visualizations to users have recently become a topic of active interest in the database and humancomputer interaction community [69]. Recent systems including SeeDB [50], Voyager [67], and ZenVisage [59] focus on recommending visualizations for large-scale data sets, particularly for exploratory analysis of relational data [47]. In this paper, we focus on the visualization of deviations within time series.…”
Section: Related Workmentioning
confidence: 99%
“…Data visualization management systems that automate and recommend visualizations to users have recently become a topic of active interest in the database and humancomputer interaction community [69]. Recent systems including SeeDB [50], Voyager [67], and ZenVisage [59] focus on recommending visualizations for large-scale data sets, particularly for exploratory analysis of relational data [47]. In this paper, we focus on the visualization of deviations within time series.…”
Section: Related Workmentioning
confidence: 99%
“…There has been work such as [19,20] on recommending visual encodings for different types of data. Tools like VISO [25] use semantic ontologies to recommend visualizations, while those like Voyager [39] focus on the interface design aspects for exploratory data analysis. Another type of visualization recommendation is performed by systems like Profiler and Scorpion [15,40] which detect specific patterns (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…We discovered that VisUnit cannot be used to replicate the controlled user studies reported by 16% of the 101 surveyed papers that have appeared in IEEE Information Visualization (InfoVis) between 1995 and 2015 such as these papers [117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132].…”
Section: Discussion Of the Limitations Of Visunitmentioning
confidence: 99%
“…For example, studies that involve eye-tracking or studies that use think-aloud protocols cannot currently be supported by VisUnit [121,129,130,131]. Similarly, user studies that measure other variables apart from accuracy and completion time cannot be supported effectively by VisUnit.…”
Section: User Studies Involving Complex Visualization Tools or Non-wementioning
confidence: 99%
See 1 more Smart Citation